1994
DOI: 10.1093/bja/72.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of percutaneous anaesthesia for venous cannulation after topical application of either amethocaine or EMLA cream

Abstract: We have compared, in a double-blind study, the efficacy of topical amethocaine cream 1 g (5% w/w) in alleviating the pain of venous cannulation with that of 5% EMLA cream 2.5 g. One hundred and twenty unpremedicated female patients undergoing minor gynaecological surgery, were allocated randomly to one of four groups: 5% EMLA cream 2.5 g for 30 min: 5% EMLA cream 2.5 g for 60 min; amethocaine cream 1 g (5% w/w) for 30 min; amethocaine cream 1 g (5% w/w) for 60 min. After removal of the cream, venous cannulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 0 publications
2
38
1
Order By: Relevance
“…23 However one study using a 5% preparation reported no significant erythema. 24 One hour was chosen as the application time for both EMLA and Ametop TM. This complied with manufacturers recommendations i.e.…”
Section: Discussionmentioning
confidence: 99%
“…23 However one study using a 5% preparation reported no significant erythema. 24 One hour was chosen as the application time for both EMLA and Ametop TM. This complied with manufacturers recommendations i.e.…”
Section: Discussionmentioning
confidence: 99%
“…If the study presented results in bar graph format, 21-23 2 reviewers independently extracted numeric data through measurement of the graphs with a ruler, and these results were averaged. In 2 papers, 22,23 SDs were calculated from individual pain scores. In 1 article, 23 the SD was calculated from the 95% confidence interval (CI).…”
Section: Methodsmentioning
confidence: 99%
“…Topical anaesthetic agents have been shown to relieve distress in children [2][3][4] and adults [5] during venepuncture and venous cannulation, as well as proving effective in capillary heel prick blood sampling in neonates [6] .…”
Section: Introductionmentioning
confidence: 99%